Synthesis and enhanced electrochemical performance of Li2CoPO4F cathodes under high current cycling - Kim, G. J. (2013)
Lithium cobalt fluorophosphate, Li2CoPO4F, is successfully synthesized by a solid state reaction under Ar flow at 700 °C. X-ray diffraction and scanning electron microscopic studies are utilized to analyze the structural and morphological features of the synthesized materials, respectively. The presence of fluorine is also supported by energy-dispersive X-ray spectroscopy. The electrochemical properties are evaluated by means of Li/Li2CoPO4F half-cell configurations in both potentiostatic and galvanostatic modes. The Li/Li2CoPO4F cell delivers an initial discharge capacity of 132 mA h g−1 at a current density of 0.1 mA cm−2 between 2.0 and 5.1 V at room temperature. Due to the higher operating potential of the Co2+/3+ couple in the fluorophosphate matrix, this cell shows a capacity retention of only 53% after 20 cycles, still the material delivered 108 mA h g−1 at a high current rate of 1 C. Cyclic voltammetric studies corroborate the insertion and extraction of Li+ ions by a single phase reaction mechanism during cycling.